Pengembangan Bahan Ajar Mata Kuliah Kurikulum dan Pembelajaran Untuk Meningkatkan Prestasi Belajar - Buyung Buyung (Universitas Batanghari Jambi, 2022)
The research objective is to develop curriculum and learning teaching materials. The research method uses research and development (R&D). The teaching material development model used is the Instructional Development model. The target subjects are undergraduate students in study programs at FKIP UNIB. This research was conducted at the Faculty of Teacher Training and Education in the odd semester of 2022/2023. Collecting data using questionnaires, interviews and observations. The results of the study based on validation by media experts and design experts showed a feasible category. In the evaluation of one to one learning, and small groups are also feasible to use. In the field trial, teaching materials were tested by giving pre and post tests with a Sig (2-tailed) test result of 0.032. The value of sig (2-tailed) < 0.05, then there is a significant difference between learning achievement in pre-test and post-test data on curriculum and learning teaching materials, meaning that teaching materials can improve learning achievement. From the results of the validation and testing carried out, it can be concluded that the curriculum and learning teaching materials are suitable for use